Effect of Exercise Programs on Fear of Falling in Multiple Sclerosis: A Systematic Review and Meta-analysis of Randomized Clinical Trials - Parisa Sedaghati (Guilan University of Medical Sciences, 2021)
Background: Multiple Sclerosis (MS) is one of the most common diseases of the Central Nervous System (CNS). Numerous studies have reported Fear of Falling (FOF) among MS patients. FOF is a factor limiting physical activity. Regular physical activity is very important for maintaining good health and preventing the complications of MS patients and can make these people more active and reduce FOF. Objectives: The aim of the present study was to do a meta-analyze about the effect of exercise programs on FOF among MS patients Materials & Methods: Primary sources were obtained from 9 databases including, PubMed, EMBASE, SCOPUS, LILACS, CINAHL, CENTRAL, Web of Science, PEDro, and Google Scholar, from inception until April 2021. Data analysis was carried out using Comprehensive Meta-Analysis ver. 2. Results: Nine studies with 350 participants were included in the review. The results of the meta-analysis showed the effect of exercise programs on the FOF among MS patients. The Hedges’ adjusted Effect Size (ES) regarding the effects of exercise programs on FOF among MS patients was -0.15 (95%CI: -0.52 - 0.22). The results of the meta-analysis showed no significant difference between the effect of exercise programs on FOF among MS patients (p=0.44). Conclusion: It was found that all exercise programs have a significant effect on FOF among MS patients. There was no statistically significant difference between exercise programs regarding which exercise programs led to a higher reduction in FOF among these patients; however, Pilates and virtual reality exercises were more effective than other exercise programs.